2015
DOI: 10.1097/nne.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Problem-Based Learning Exercise to Teach the Lean 8-Step Problem-Solving Method

Abstract: Doctor of nursing practice (DNP) graduates must be prepared to lead quality improvement (QI) initiatives in health care settings; however, effective and feasible teaching strategies pose a challenge for many DNP program faculties. This article describes a successful and practical problem-based learning exercise for students to work through the QI process using the Lean 8-step problem-solving method. Suggestions for faculty and recommendations for future activities are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Conger and Miller (2014) use Lego coupled with PBL to teach LM in classroom. Tovar and Warshawsky (2015) integrate PBL to more assertively teach LM to nursing doctoral graduates. Kanigolla et al (2014) identified how PBL influences students' LM learning, based on a survey after the project’s completion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conger and Miller (2014) use Lego coupled with PBL to teach LM in classroom. Tovar and Warshawsky (2015) integrate PBL to more assertively teach LM to nursing doctoral graduates. Kanigolla et al (2014) identified how PBL influences students' LM learning, based on a survey after the project’s completion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 papers were retrieved for evaluation with respect to the inclusion criteria and methodological quality. 4 out of 11 papers did not focus on nursing students, and 2 cases were excluded from this literature review since it focuses on Doctor of nursing practice (DNP) graduates [11] rather than undergraduate nursing students. Thus, five articles were included in this scoping review, comprising two systematic review, two quasi-experimental studies, one observational analytic study (Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…It provides the basis for life-long learning and is becoming increasingly dominant in nursing education field [8]. People hypothesised that PBL would work more effectively and successfully as an innovative teaching method competing to traditional lecture tutorials [9][10][11][12][13]. Indeed, some evidence has reported PBL produced clear benefits for nursing students, such as increased autonomous learning, critical thinking, problem-solving skills and communication [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conger & Miller (2014) complement this approach by illustrating how Lego exercises, when coupled with PBL, provide a useful framework for students to transfer their knowledge from the classroom to a lean six sigma project. Tovar & Warshawsky (2015) expand the discussion by introducing a PBL exercise to teach LM principles and techniques to other courses than engineering. Specifically, the authors describe PBL application with nursing doctoral graduates to work through the quality improvement process using the lean 8-step problem-solving method.…”
Section: Teaching and Learning Of Lean Manufacturingmentioning
confidence: 99%